2018
DOI: 10.1002/ppsc.201800265
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Photothermal Hydrogen Production from Glycerol Aqueous Solutions over Noble Metal‐Free Ti@TiO2 Core–Shell Nanoparticles

Abstract: Photocatalytic production of hydrogen from renewable sources with platinum group metal‐free catalysts is of great importance for environmentally friendly energetics. Herein, Ti@TiO2 core–shell nanoparticles prepared by sonohydrothermal treatment of titanium metal nanoparticles are examined for hydrogen generation from aqueous glycerol solutions under vis/NIR light irradiation. It is shown that photocatalytic reforming of glycerol in the presence of Ti@TiO2 exhibits strong photothermal effect allowing more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…Among Ti@TiO 2 NPs, the sample obtained at 214 • C displays the lowest R 2 value indicating the fastest charge transfer rate for this material. This conclusion is in an agreement with an effective charge separation in Ti@TiO 2 NPs recently demonstrated using photoluminescence spectroscopy (Nikitenko et al, 2018).…”
Section: Light Absorption and Charge Transfersupporting
confidence: 91%
See 3 more Smart Citations
“…Among Ti@TiO 2 NPs, the sample obtained at 214 • C displays the lowest R 2 value indicating the fastest charge transfer rate for this material. This conclusion is in an agreement with an effective charge separation in Ti@TiO 2 NPs recently demonstrated using photoluminescence spectroscopy (Nikitenko et al, 2018).…”
Section: Light Absorption and Charge Transfersupporting
confidence: 91%
“…Stable Ti@TiO 2 NPs were prepared by SHT treatment of Ti nanopowder in pure water (Milli-Q 18.2 M •cm at 25 • C). The SHT reactor is shown in Supplementary Figure 1 and described previously (Cau et al, 2013;Nikitenko et al, 2015Nikitenko et al, , 2018. In a typical experiment, 2 g of air passivated Ti nanopowder was dispersed in 50 mL of water using ultrasonic bath, placed in SHT reactor and heated at selected temperatures in the range of T = 100-214 • C (autogenic pressure P = 1.0-19.0 bar) under simultaneous ultrasonic treatment (f = 20 kHz, P ac = 17 W) for 3 h. After cooling, the treated NPs were recovered by centrifugation, washed with pure water and dried at room temperature under reduced pressure.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we report, for the first time, sonocatalytic AOP of EDTA using nanoparticles (NPs) of metallic titanium, Ti 0 , and core-shell Ti@TiO 2 NPs. It has been recently shown that Ti@TiO 2 NPs exhibit strong photothermal effect in the process of photocatalytic hydrogen production from aqueous solutions of methanol [8] and glycerol [9] . Photocatalytic activity of core-shell Ti@TiO 2 NPs has been attributed to the effective charge separation [(TiO 2 h+ )(Ti e− )], where h + in photoexcited core-shell particles.…”
Section: Introductionmentioning
confidence: 99%